ANALISIS TINGKAT KEMATANGAN SISTEM INFORMASI PENERIMAAN MAHASISWA BARU - Dwi Vernanda (Jurnal Ilmiah Ilmu dan Teknologi Rekayasa, 2020)
The use of information systems for institutional management is to help management in knowing what causes the institution's target to be achieved or not achieved. The new student admission process (PMB) is a routine activity carried out by a university every year to get new students. Subang State Polytechnic (POLSUB) utilizes technology in the form of information systems in PMB activities, especially for online registration processes, announcement of results, management of administrative data, and information on PMB.The Importance of the New Student Admissions Information System (SI PMB), there arises interest in discussing and analyzing whether the current PMB SI has been in accordance with the function and checking whether SI PMB can help complete the work in accordance with the objectives. The study was conducted to create a model that can analyze the application of SI PMB by utilizing Operation Management Technique (OMT) and the Capability Maturity Model (CMM) theory as a benchmark of success. This research is still in the process of processing, a temporary product is a model that contains the determination of variables and measuring indicators that will be used in measuring the maturity of the New Student Admissions Information System, as well as the instrument of questions that will be filled by previously determined respondents. The models and instruments made are expected to be used to analyze the maturity of the New Student Admissions Information System at Subang State Polytechnic.Keywords: Maturity Model, Operations Management Technique, New Student Admission.